ILMe (I Love Me): Psikoedukasi tentang Persepsi Citra Tubuh pada Siswi Sekolah Menengah Atas - Lionita, Widya; Arinda, Ditia Fitri; Appulembang, Yeni Anna; Anggraini, Rini (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2021)
Background: Nutrition status among girls is becoming a severe concern for preventing undernutrition in their future pregnancy. Since they experience many physical changes during adolescence, some girls will feel dissatisfied with their own body. This feeling may lead to negative body image, which is a long time will impact health status. The research aimed to facilitate psychoeducation and analyze the improvements towards the senior high school girls’ perception of body image in Palembang.Method: A quasi-experimental study design was employed in the research with a non-equivalent control group. Participants were selected using purposive sampling, divided into intervention (n=18) and control (n=19) groups. All steps of the research were carried out online because of pandemic COVID-19. The questionnaire was given via Google form, while the three psychoeducation sessions were given through Zoom Meetings. Data were analyzed using Paired T-test (intervention) and Wilcoxon Signed Rank Test (control).Results: Most of the participants are 16 years old (40%), first-grade students (46%), and go to public school (67%). The mean score of both groups is decreased, which indicate their perception of body image is changed positively. However, there was no significant mean difference of the perception before and after treatment, either intervention (p-value 0.632) or control group (p-value 0.494). By the psychoeducation session, some participants already tried to share their feelings and problems related to their bodies, mostly originating from negative opinions given by peers. Girls should be motivated to love themselves through psychoeducation sessions with longer duration or more frequency to generate a positive body image.